2011
DOI: 10.5581/1516-8484.20110104
|View full text |Cite
|
Sign up to set email alerts
|

Aceruloplasminemia

Abstract: Aceruloplasminemia is a rare autosomal recessive disease in which a mutation leads to the absence or dysfunction of ceruloplasmin. Deficiency of this enzyme leads to the accumulation of iron in various organs; aceruloplasminemia is usually characterized by diabetes, retinal degeneration and neurological disorders. Diagnosis is suspected by the presence of elevated levels of ferritin, anemia, decreased serum copper and absence of ceruloplasmin in serum. Treatment of aceruloplasminemia is mainly based on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…As it was mentioned above, by binding to Cp, copper stimulates its ferroxidase activity and participates in iron homeostasis, so it may be hypothesized that some indirect toxicity mediated by altered iron concentrations may be a consequence of low copper levels. Accordingly, aceruloplasmemia, an autosomal recessive disease characterized by Cp deficiency and caused by mutations in the CPN gene, is associated with iron accumulation in the pancreas, liver, basal ganglia, and retina [217]. In addition, brain iron accumulation has been reported to be associated with the loss of neurons in the same regions, and the effects appear be associated with the ability of ferrous ions to enhance oxidative stress conditions.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…As it was mentioned above, by binding to Cp, copper stimulates its ferroxidase activity and participates in iron homeostasis, so it may be hypothesized that some indirect toxicity mediated by altered iron concentrations may be a consequence of low copper levels. Accordingly, aceruloplasmemia, an autosomal recessive disease characterized by Cp deficiency and caused by mutations in the CPN gene, is associated with iron accumulation in the pancreas, liver, basal ganglia, and retina [217]. In addition, brain iron accumulation has been reported to be associated with the loss of neurons in the same regions, and the effects appear be associated with the ability of ferrous ions to enhance oxidative stress conditions.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The use of a chelating agent, such as oral deferiprone (DFP), was shown to be protective against the increased oxidative stress and retinal degeneration ( Hadziahmetovic et al, 2011 ; Wolkow et al, 2012 ). Despite the good results obtained in the mouse model, the use of DFP on a patient resulted in a worsening of symptoms ( Mariani et al, 2004 ), while variable results ranging from mild amelioration to no effect on neurological symptoms were obtained in patients treated with deferasirox ( Skidmore et al, 2008 ; Roberti Mdo et al, 2011 ). However iron-chelating therapy appeared effective in reducing the hepatic and pancreatic iron overload ( Finkenstedt et al, 2010 ).…”
Section: Nbia Caused By Defects In Genes Coding For Proteins Of Iron mentioning
confidence: 99%
“…The effectiveness of iron chelation therapy has been described in previous reports ( 8 , 19 - 21 ). Additionally, some reports have suggested that iron chelation therapy is effective for hepatic iron overload, diabetes mellitus, and neurological symptoms, but not for improving iron accumulation, which can be observed on brain MRI ( 15 , 22 , 23 ). In our case, the AST and ALT levels were found to be elevated at the time of her first visit to the Department of Gastroenterology, and phlebotomy therapy and the discontinuation of oral iron supplements were carried out to treat her liver hemosiderosis.…”
Section: Discussionmentioning
confidence: 99%